A Versatile Calcium Phosphate Nanogenerator for Tumor Microenvironment‐activated Cancer Synergistic Therapy. Issue 23 (10th October 2021) - Fu, Lian‐Hua; Li, Chunying; Yin, Weimin; Hu, Yan‐Ru; Sun, Tuanwei; Wan, Yilin; Lin, Jing; Li, Zhiming; Huang, Peng
Abstract: Gas therapy is an emerging "green" cancer treatment strategy; however, its outcome often restricted by the complexity, diversity, and heterogeneity of tumor. Herein, a tumor targeting and tumor microenvironment‐activated calcium phosphate nanotheranostic system (denoted as GCAH) is constructed for effective synergistic cancer starvation/gas therapy. GCAH is obtained by a facile biomineralization strategy using glucose oxidase (GOx) as a biotemplate, followed by loading of l ‐Arginine ( L ‐Arg) and modification of hyaluronic acid (HA) to allow special selectivity for glycoprotien CD44 overexpressed cancer cells. This nanotheranostic system not only exhausts the glucose nutrients in tumor region by the GOx‐triggered glucose oxidation, the generated H2 O2 can oxidize L ‐Arg into NO under acidic tumor microenvironment for enhanced gas therapy. As such, there are significant enhancement effects of starvation therapy and gas therapy through the cascade reactions of GOx and L ‐Arg, which yields a remarkable synergistic therapeutic effect for 4T1 tumor‐bearing mice without discernible toxic side effects. Abstract : In this work, a tumor targeting and tumor microenvironment‐activated calcium phosphate nanotheranostic system (denoted as GCAH) is constructed for effective synergistic cancer starvation/gas therapy.